A novel multiplex polymerase chain reaction assay for detection of both HLA‐A*31:01/HLA‐B*15:02 alleles, which confer susceptibility to carbamazepine‐induced severe cutaneous adverse reactions. (2nd October 2017) - Nguyen, D. V.; Vidal, C.; Chi, H. C.; Do, N. T. Q.; Fulton, R.; Li, J.; Fernando, S. L.
Abstract : HLA‐A*31:01 and HLA‐B*15:02 have been widely reported to confer genetic susceptibility to carbamazepine (CBZ)‐induced severe cutaneous adverse reactions (SCARs). Accordingly, the screening for these alleles has been highly recommended to prevent SCAR prior to introducing CBZ therapy. Although a number of methods are available for screening of HLA‐A*31:01 or HLA‐B*15:02 alleles separately, developing an assay that can detect both these alleles would be more clinically practical, cost‐effective and less time‐consuming. Therefore, in this study, a multiplex polymerase chain reaction (PCR) using TaqMan Probe was designed and validated to be able to detect HLA‐A*31:01 and HLA‐B*15:02. In comparison with Luminex‐SSO/SBT/SSB, the multiplex PCR assay for detection of HLA‐A*31:01 and HLA‐B*15:02 had a perfect agreement in the validation group of 125 samples. The method was able to detect the target genes at the DNA concentration of 0.037 ng/μL. The unit cost of this assay is less than 5 USD with total time of 110 minutes.